Renovación urbana en el sector de las delicias como estrategia articuladora para crear una conexión de ciudad en el municipio de Palmira - Valle (2022)
This research work was born in a class of theory and history of the territory, when it became known that there is a study by the CITCE of the university of the valley where it reflects four partial plans through basic schemes to create a compact center in the municipality of Palmira, after knowing all this, we took the initiative to know much more about the partial plan of delights and we began to see how within the renovation polygon there are two facilities, the existence of a small park but when visiting the sector we see how in the sector is evident the deteriorated, urban and also architecturally; being within this problem a facility such as the old Champagnat college.